The Restrictions on Predictability Implied by Rational Asset Pricing Models - Kirby, Chris (Review of Financial Studies, 1998)
Journal Article The Restrictions on Predictability Implied by Rational Asset Pricing Models Get access Chris Kirby Chris Kirby University of Texas at Dallas Address correspondence to Chris Kirby, School of Management, University of Texas at Dallas, P.O. Box 830688, Richardson, TX 75083-0688. Search for other works by this author on: Oxford Academic Google Scholar The Review of Financial Studies, Volume 11, Issue 2, April 1998, Pages 343–382, https://doi.org/10.1093/rfs/11.2.343 Published: 03 June 2015